2013
DOI: 10.1155/2013/951795
|View full text |Cite
|
Sign up to set email alerts
|

Antiurolithiatic Activity of Extract and Oleanolic Acid Isolated from the Roots of Lantana camara on Zinc Disc Implantation Induced Urolithiasis

Abstract: The present study was done to evaluate the antiurolithiatic activity of ethanolic extract of roots (ELC 200 mg/kg) and oleanolic acid (OA 60 mg/kg, O.A. 80 mg/kg, O.A. 100 mg/kg) isolated from roots of Lantana camara in albino wistar male rats using zinc disc implantation induced urolithiatic model. The group in which only zinc disc was implanted without any treatment showed increase in calcium output (23  ± 2.7 mg/dL). Cystone receiving animals showed significant protection from such change (P < 0.01). Treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…[19] Thus, this study involves the induction of hyperoxaluria in male albino rats with the oral administration of EG which stimulates the nidus formation, calcium oxalate saturation, crystal aggregation, and retention within kidney tubules. [20] Male rats were selected for the study due to resemblance of urinary system with the human and also earlier studies have shown that frequency of stone deposition was significantly high in male as compare to female rats. [21] This study demonstrates that ethanolic root extract and petroleum ether fraction showed good antiurolithic activity in a dosedependent manner as compared the standard drug cystone.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Thus, this study involves the induction of hyperoxaluria in male albino rats with the oral administration of EG which stimulates the nidus formation, calcium oxalate saturation, crystal aggregation, and retention within kidney tubules. [20] Male rats were selected for the study due to resemblance of urinary system with the human and also earlier studies have shown that frequency of stone deposition was significantly high in male as compare to female rats. [21] This study demonstrates that ethanolic root extract and petroleum ether fraction showed good antiurolithic activity in a dosedependent manner as compared the standard drug cystone.…”
Section: Discussionmentioning
confidence: 99%
“…[26] This suggests obstruction of urinary bladder due to the formation of urinary calculi. In this study, the CAM and MAM treatment increased urine output, and this may be due to prevention of stone formation or their direct diuretic effect which reduced supersaturation of urine with precipitating substances and thereby stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Then the rats were sacrificed and zinc disc implants/stones were removed from the bladder and dried. Stones taken out were weighed [6][7][8][9][10] .…”
Section: Surgical Procedurementioning
confidence: 99%